Modelo numérico de efeitos hidrodinâmicos em escoamentos internos e externos - Ahumada Fonfach, José Miguel (2017)
This work develops a numerical model for external and internal flows to a ship under regular waves. The numerical model consists of the coupling of two methods with different nature, which were evaluated independently in a first stage. The first one is the time domain method based on the panel method and potential theory to calculate the ship dynamic in regular waves; here the formulation of ship motion equations considers nonlinear terms and the Froude-Krilov force is extrapolated to the instantaneous free surface. The time domain method was evaluated in a simple case of a box shape under transversal and longitudinal waves, analyzing the roll, heave and pitch motion amplitudes. The other method was a particles method based on the Euler equations, specifically the called I-MPS (Improved Moving Particle Semi-implicit) to study the internal flow with complex free surfaces. The I-MPS includes a new formulation for the boundary condition on the walls; several cases of internal flow, dambreak, sloshing and sloshing with mass transfer in a 2D box were studied and compared with experimental results, showing good results.